Determinants of Work Productivity: The Roles of Health and Lifestyle among Government Employees - Wafa Ma'mun; Isna Qadrijati; Adi Magna Patriadi Nuhriawangsa (Media Publikasi Cendekia Indonesia, 2026)
Work productivity is an important aspect for workers and institutions that is influenced by internal factors such as education level, discipline, attitude, work motivation, health, nutrition, and physical condition, as well as external factors associated with the environment, including workplace conditions, organizational policies, wages, and infrastructure. This study aims to determine the relationship between physical fitness, sedentary behavior, nutritional status, and breakfast habits with the work productivity of employees at the Ministry of Religious Affairs in Central Java Province. This study used a quantitative method with a cross-sectional design. A sample of 101 employees was selected using purposive sampling. Questionnaires were used to collect data on work productivity, sedentary activities, and breakfast habits. Physical fitness was measured using the YMCA step test method, and nutritional status was measured using body mass index. Data were analyzed using SPSS with Somers' D test and ordinal logistic regression. The results show that there is a significant relationship between physical fitness, breakfast habits, and nutritional status with work productivity while sedentary behavior is not related to work productivity. In conclusion, physical fitness, breakfast habits, and nutritional status are related to the work productivity of employees at the Ministry of Religious Affairs in Central Java Province.